POLITICAL CONFLICT AND COMPROMISE IN THE JOB CREATION BILL DISCUSSION - M. Masad Masrur; Umaimah Wahid; Morissan, Morissan (International Journal of Social Science, 2024)
Regulatory reform by amending various provisions in dozens of laws into a single Omnibus Law on Job Creation has been rejected because it is considered to eliminate protection for workers/labourers, and expand the dominance of employers. The wave of rejection continues to strengthen, raising questions about the process of political communication, conflict and negotiation, and political compromise between political forces in the DPR (Parliamentary Institutions). With a constructiveist paradigm and case study method, and supported by several theories from political science, political communication, negotiation theory, conflict theory, as well as several concepts regarding political compromise, the results showed that political communication in the discussion of the Job Creation Bill took place systematically by placing the authority of political parties as decision makers. Political conflict occurs due to inflexible negotiations. Political negotiations carried out through a principle-based negotiations approach, although it can accelerate the discussion process, is unable to guarantee the effectiveness of political compromise. The Job Creation Bill comes as an orthodox legal product and was declared unconstitutional by the Constitutional Court. Four things that become the findings of this research are (1) the dynamics of political communication are strongly influenced by the presidential-multiparty political system that produces majoritarian power, so that it has consequences for political alignments; (2) political conflicts that arise due to polarisation of political support have presented inflexible political communication, (3) principle-based political negotiations are pragmatically able to accelerate discussions but do not guarantee resistance/rejection by the public; and (4) political compromise through the stages of strategy development, relationship management, and decision making, cannot be a form of agreement that can accommodate all parties